The blended learning model with online skills on the learning independence of high school students - Mesta Limbong; Jitu Halomoan Lumbantoruan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The research aims to determine the effectiveness of blended learning management and online skills on student learning independence in the North Tapanuli region. The low learning interaction between teachers and students is caused by restrictions and forcing students to study independently. Therefore, teachers must develop competence by presenting the right model. Teachers have no other choice but to carry out good blended learning management so that learning activities continue. The method in this research is quantitative with the type of ex post facto research, namely comparative causal research. Data collection techniques by distributing instruments in the form of questionnaires to teacher respondents. The population in this study were all teachers in North Tapanuli Regency with a sample of 90 people from 4 schools that were spread out. Data analysis techniques are correlation and regression. The results of the study show that blended learning management and online skills have an impact on student learning independence. The effect of the blended learning model on students' online skills is 52.10%. Conclusion in increasing student learning independence, teachers use blended learning models to the fullest. However, this model must still be supported by the provision of online student skills.